To generate the equivalent expression \( 314 \) from \( 353 - 9 \), the following properties of exponents were used:
-
Property of Negative Exponents: This property states that \( a^{-n} = \frac{1}{a^n} \). In this case, if we interpret \( 353 - 9 \) as \( 3^{53} \cdot 3^{-9} \) (since \( 3^{-9} = \frac{1}{3^9} \)), it results in division.
-
Product Rule of Exponents: This rule states that \( a^m \cdot a^n = a^{m+n} \). Therefore, \( 3^{53} \cdot 3^{-9} = 3^{53 - 9} = 3^{44} \).
To find \( 314 \), we can represent it as \( 3^{44} \) based on the manipulation shown.
So, the correct response is: the Property of Negative Exponents and the Product Rule of Exponents.